Development and Innovation of Qur'anic Learning Methodologies in Indonesia - Sulistyowati, Sulistyowati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
The methodology of Qur'anic learning in Indonesia has evolved from traditional approaches to innovations based on modern technology, in line with social changes and technological advancements. This study aims to analyze the historical development, recent innovations, and the strengths and challenges of Qur'anic learning methodologies in Indonesia. Using a library research method, data were qualitatively analyzed from various primary and secondary references, including previous studies and relevant books. The results show that traditional methods such as sorogan and bandongan are still practiced in Islamic boarding schools, while modern technology-based methods, such as digital applications, e-learning, and interactive multimedia, are trending in formal educational institutions. These innovations offer advantages such as broader access and more flexible learning processes but face challenges like the digital divide and the need for continuous teacher training. The implications of this study highlight the necessity of a hybrid approach that integrates traditional values with technological innovations to balance Qur'anic reading skills and spiritual character development. The study contributes both theoretically and practically by providing recommendations for adaptive curriculum development and technology-based teacher training. The originality of this research lies in its exploration of the integration of traditional and modern methods as a sustainable solution for Qur'anic learning in the digital era.